EARLY DETECTION KEY TO PREVENTION OF TERRORISM ACTIVITIES - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 10 March 2016 – Terroristrelated issues occurring in Europe, Africa, the Americas and Asia have created a sense of urgency for the global community to be more vigilant on the potential threats from terrorists.